Efferent projections of topographically distinct relaxin family peptide receptor-3 (RXFP3) lateral hypothalamus/zona incerta cells - Brandon K. Richards; Alexander I. J. Kilby; Jennifer L. Cornish; Jee Hyun Kim; Andrew J. Lawrence; Christina J. Perry (Brain Structure and Function, 2026)
Relaxin family peptide receptor-3 (RXFP3) is a ligand-activated G-protein coupled receptor and the cognate receptor for the conserved neuropeptide relaxin-3. We recently demonstrated that chemogenetically activating an RXFP3-expressing population in the lateral hypothalamus and zona incerta (LH/ZI RXFP3 ) induced escape-like jumping behaviour following fear conditioning, but only in a subset of mice. Given the diverse hodology of the LH and ZI, we hypothesised that LH/ZI RXFP3 cells may consist of discrete subpopulations with unique connectivity patterns that govern different aspects of defensive behaviour. To explore this possibility, we unilaterally injected small volumes of a Cre-dependent anterograde viral tracer into four distinct sites of the LH/ZI in RXFP3-Cre mice and analysed their brain-wide efferent connectivity patterns. Each injection site group produced unique projection patterns, particularly to nuclei involved in threat and defensive behaviour. Of note were strong projections from the rostral ZI and anterior LH to the lateral habenula, and projections from the intermediate and caudal ZI to the ventrolateral periaqueductal gray. By combining retrograde tracing and RNAscope fluorescent in situ hybridisation, we identified that most LH/ZI RXFP3 projections to the lateral habenula arose from a subset of vGlut2-expressing lateral hypothalamus neurons, while most projections to the ventrolateral periaqueductal gray arose from a subset of GAD1-expressing zona incerta neurons. Taken together, our results strongly suggest that LH/ZI RXFP3 cells exhibit distinct efferent projection patterns throughout the brain depending on their topographical location within these nuclei, likely reflecting the functional diversity of these neurons.

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Alaska visitors’ knowledge about invasive species in a warming arctic and sub-arctic - Michele Remer; Izabella R. Block; Elizabeth E. Perry; Jennifer I. Schmidt; Jianguo Liu (Biological Invasions, 2026)
As the climate warms and sea ice continues to melt, an increase in overall shipping traffic to the Arctic and to local communities is expected. Specifically, an increase in cruise ship traffic has led to higher numbers of visitors to the Arctic and sub-Arctic. As a secondary effect of increased human activity in this region, invasive species prevention and removal will become a priority, especially as species’ ranges continue to shift with the warming climate. Thus, it is important to have a baseline of visitor knowledge about invasive species in the region to promote robust monitoring. To evaluate visitor knowledge, we conducted visitor intercept surveys in three Alaskan communities that experience tourism. Results show that owning watercraft is associated with an increase in knowledge, but increased knowledge did not lead to any changes in behavior. In addition, increased invasive species knowledge did not differ between visitor groups. Our research demonstrates the need to consider the potential spread of invasive species due to tourism and a need to focus on both systemic policy changes and educational campaigns to encourage cleaning gear brought on travels.

Neighborhood environmental vulnerability factors strongly drove COVID-19 fatality and excess all-cause mortality in New York City, while long-term air pollutant associations were weak and varied - Alexander Azan; Sneha Kannoth; Cong Zhang; Mehr Shafiq; Earle C. Chambers; Perry E. Sheffield; Sandra S. Albrecht; Azure Thompson; Jennifer Woo Baidal; Min Qian; Stephanie Lovinsky-Desir; Jeanette A. Stingone (Science of The Total Environment, 2025)

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Air Pollution and Temperature in Seizures and Epilepsy: A Scoping Review of Epidemiological Studies - Rachit Sharma; Leah H. Schinasi; Brian K. Lee; Jennifer Weuve; Marc G. Weisskopf; Perry E. Sheffield; Jane E. Clougherty (Current Environmental Health Reports, 2024)
Purpose of the Review Seizures and epilepsy can be debilitating neurological conditions and have few known causes. Emerging evidence has highlighted the potential contribution of environmental exposures to the etiology of these conditions, possibly manifesting via neuroinflammation and increased oxidative stress in the brain. We conducted a scoping review of epidemiological literature linking air pollution and temperature exposures with incidence and acute aggravation of seizures and epilepsy. We systematically searched PubMed, Embase, Web of Science, and APA PsycINFO databases for peer-reviewed journal articles published in English from inception to February 7, 2024. Recent Findings We identified a total of 34 studies: 16 examined air pollution exposure, 12 ambient temperature, and six examined both air pollution and ambient temperature. Most studies were conducted in Asia (China, Taiwan, South Korea, and Japan). Nearly all studies retrospectively derived acute (daily average), ambient, and postnatal exposure estimates from ground monitoring systems and ascertained epilepsy cases or seizure events through record linkage with medical records, health registry systems, or insurance claims data. Commonly assessed exposures were particulate matter (PM 2.5 , PM 10 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), carbon monoxide (CO), ozone (O 3 ), and daily mean ambient temperature. Overall, the main findings across studies lacked consistency, with mixed results reported for the associations of air pollutants and temperature metrics with both seizure incidence and acute aggravations of epilepsy.

Evaluating the efficacy of targeted traffic management interventions: A novel methodology for determining the composition of particulate matter in urban air pollution hotspots - Hamesh Patel; Perry Davy; Cherie Tollemache; Nick Talbot; Jennifer Salmond; David E. Williams (Science of The Total Environment, 2024)

Diet choice is insensitive to mating in male fruit flies - Mabel C. Sydney; Tracey Chapman; Jennifer C. Perry (Animal Behaviour, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Quantification of CD3, FoxP3, and granzyme B immunostaining in canine renal cell carcinoma - Ashleigh Cournoyer; Hayley Amerman; Charles-Antoine Assenmacher; Amy Durham; James A. Perry; Allison Gedney; Nicholas Keuler; Matthew J. Atherton; Jennifer A. Lenz (Veterinary Immunology and Immunopathology, 2024)

A mobile monitoring method for the screening of vehicle-movement-induced airborne erionite from roads in high-development residential areas - Nick Talbot; Hamesh Patel; Seosamh B. Costello; Perry Davy; Jennifer Salmond; Martin Brook; Kim Dirks (Atmospheric Pollution Research, 2024)

Using environmental health dialogue in a Diné-centered approach for individualized results reporting in an environmental exposure study following the Gold King Mine Spill - Yoshira Ornelas Van Horne; Stephanie Russo Carroll; Karletta Chief; Nathan Z. Lothrop; Jennifer R. Richards; Mae-Gilene Begay; Perry H. Charley; Jani C. Ingram; Paloma I. Beamer (Environmental Research, 2023)

Examining the performance of alternative harvest regulations for short-lived taxa: A case study of Florida Bay scallop management - Lisa Chong; Nicholas Fisch; John Scott Borsum; Jennifer Granneman; Diana Perry; Gabrielle Love; Brittany Hall-Scharf; Robert Botta; Kai Lorenzen; Edward Camp; Zachary Siders (Fisheries Research, 2023)

Effect of post-harvest processing methods on the microbial safety of edible seaweed - Jessica G. Vorse; Colleen T. Moody; Lyle C. Massoia; Jennifer J. Perry; Kristin M. Burkholder; Carrie J. Byron (Journal of Applied Phycology, 2023)
The American seaweed industry is growing, primarily into the edible sector, and more seaweed products are available for human consumption. It is necessary to evaluate the safety of industry’s current post-harvest storage and processing methods to ensure the risk of foodborne pathogens on edible seaweed remains low. We evaluated the pathogen load of edible kelp post-harvest under three different storage temperatures (4˚C, 10˚C, 20˚C) and two different drying methods (air- and freeze-drying). The focal pathogens for this research included: Listeria monocytogenes, Salmonella enterica, Staphylococcus aureus, pathogenic Escherichia coli, Vibrio vulnificus and Vibrio parahaemolyticus . We tested all six pathogens under each treatment condition on both sugar kelp ( Saccharina latissima) and rockweed ( Ascophyllum nodosum ) as these are the most commonly farmed and wild-harvested species in Maine, respectively. We inoculated a known concentration of pathogen onto freshly harvested kelp, treated it under a storage temperature or drying method, and sampled it over time to determine the impact of treatment on pathogen load. Our results showed that storage at 20˚C can lead to replication while storage at 4˚C and 10˚C halted the replication of focal pathogens. Both air-drying and freeze-drying produced significant log scale reductions in surface pathogen load for all focal pathogens. Additionally, air-drying reduced pathogen load more than freeze-drying for a majority of pathogens and storing dried kelp for 6-weeks further reduced pathogen load across all cases. These results are promising for industry as they corroborate historical evidence that current post-harvest storage and processing conditions are producing products safe for human consumption.

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Ability of rbcL and matK DNA barcodes to discriminate between montane forest orchids - Samantha J. Worthy; Kylie Bucalo; Erin Perry; Alex Reynolds; Jennifer Cruse-Sanders; Álvaro J. Pérez; Kevin S. Burgess (Plant Systematics and Evolution, 2022)

Using knowledge to care for country: Indigenous-led evaluations of research to adaptively co-manage Kakadu National Park, Australia - Cathy J. Robinson; Jennifer Mairi Macdonald; Michael Douglas; Justin Perry; Samantha Setterfield; Dennis Cooper; Maria Lee; Jonathan Nadji; Sean Nadji; Alfred Nayinggul; Anita Nayinggul; Kenneth Mangiru; et al. (Sustainability Science, 2022)

Effects of pre-freezing blanching procedures on the physicochemical properties and microbial quality of frozen sugar kelp - Samuel Akomea-Frempong; Jennifer J. Perry; Denise I. Skonberg (Journal of Applied Phycology, 2022)

The importance of 1.5°C warming for the Great Barrier Reef - Jennifer K. McWhorter; Paul R. Halloran; George Roff; William J. Skirving; Chris T. Perry; Peter J. Mumby (Global Change Biology, 2022)
Tropical coral reefs are among the most sensitive ecosystems to climate change and will benefit from the more ambitious aims of the United Nations Framework Convention on Climate Change's Paris Agreement, which proposed to limit global warming to 1.5° rather than 2°C above pre‐industrial levels. Only in the latest Intergovernmental Panel on Climate Change focussed assessment, the Coupled Model Intercomparison Project phase 6 (CMIP6), have climate models been used to investigate the 1.5° warming scenario directly. Here, we combine the most recent model updates from CMIP6 with a semi‐dynamic downscaling to evaluate the difference between the 1.5 and 2°C global warming targets on coral thermal stress metrics for the Great Barrier Reef (GBR). By ~2080, severe bleaching events are expected to occur annually under intensifying emissions (shared socioeconomic pathway SSP5‐8.5). Adherence to 2° warming (SSP1‐2.6) halves this frequency but the main benefit of confining warming to 1.5° (SSP1‐1.9) is that bleaching events are reduced further to 3 events per decade. Attaining low emissions of 1.5° is also paramount to prevent the mean magnitude of thermal stress from stabilizing close to a critical thermal threshold (8 Degree Heating Weeks). Thermal stress under the more pessimistic pathways SSP3‐7.0 and SSP5‐8.5 is three to fourfold higher than the present day, with grave implications for future reef ecosystem health. As global warming continues, our projections also indicate more regional warming in the central and southern GBR than the far north and northern GBR.

A resource-poor developmental diet reduces adult aggression in male Drosophila melanogaster - Danielle Edmunds; Stuart Wigby; Jennifer C. Perry (Behavioral Ecology and Sociobiology, 2021)
Aggressive behaviours occur throughout the animal kingdom and agonistic contests often govern access to resources. Nutrition experienced during development has the potential to influence aggressive behaviours in adults through effects on growth, energy budgets and an individual’s internal state. In particular, resource-poor developmental nutrition might decrease adult aggression by limiting growth and energy budgets, or alternatively might increase adult aggression by enhancing motivation to compete for resources. However, the direction of this relationship—and effects of developmental nutrition experienced by rivals—remains unknown in most species, limiting understanding of how early-life environments contribute to variation in aggression. We investigated these alternative hypotheses by assessing male-male aggression in adult fruit flies, Drosophila melanogaster , that developed on a low-, medium- or high-resource diet, manipulated via yeast content. We found that a low-resource developmental diet reduced the probability of aggressive lunges in adults, as well as threat displays against rivals that developed on a low-resource diet. These effects appeared to be independent of diet-related differences in body mass. Males performed relatively more aggression on a central food patch when facing rivals of a low-resource diet, suggesting that developmental diet affects aggressive interactions through social effects in addition to individual effects. Our finding that resource-poor developmental diets reduce male-male aggression in D. melanogaster is consistent with the idea that resource budgets mediate aggression and in a mass-independent manner. Our study improves understanding of the links between nutrition and aggression. Significance statement Early-life nutrition can influence social behaviours in adults. Aggression is a widespread social behaviour with important consequences for fitness. Using the fruit fly, Drosophila melanogaster , we show that a poor developmental diet reduces aspects of adult aggressive behaviour in males. Furthermore, males perform more aggression near food patches when facing rivals of poor nutrition. This suggests that early-life nutrition affects aggressive interactions through social effects in addition to individual effects.

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

Adult-onset opsoclonus-myoclonus syndrome due to West Nile Virus treated with intravenous immunoglobulin - Julien Hébert; David Armstrong; Nick Daneman; Jennifer Deborah Jain; James Perry (Journal of NeuroVirology, 2017)

Climate and edaphic controllers influence rhizosphere community assembly for a wild annual grass - Erin E. Nuccio; James Anderson‐Furgeson; Katerina Y. Estera; Jennifer Pett‐Ridge; Perry de Valpine; Eoin L. Brodie; Mary K. Firestone (Ecology, 2016)
The interface between roots and soil, known as the rhizosphere, is a dynamic habitat in the soil ecosystem. Unraveling the factors that control rhizosphere community assembly is a key starting point for understanding the diversity of plant‐microbial interactions that occur in soil. The goals of this study were to determine how environmental factors shape rhizosphere microbial communities, such as local soil characteristics and the regional climate, and to determine the relative influence of the rhizosphere on microbial community assembly compared to the pressures imposed by the local and regional environment. We identified the bacteria present in the soil immediately adjacent to the roots of wild oat ( Avena spp .) in three California grasslands using deep Illumina 16S sequencing. Rhizosphere communities were more similar to each other than to the surrounding soil communities from which they were derived, despite the fact that the grasslands studied were separated by hundreds of kilometers. The rhizosphere was the dominant factor structuring bacterial community composition (38% variance explained), and was comparable in magnitude to the combined local and regional effects (22% and 21%, respectively). Rhizosphere communities were most influenced by factors related to the regional climate (soil moisture and temperature), while background soil communities were more influenced by soil characteristics ( pH , CEC , exchangeable cations, clay content). The Avena core microbiome was strongly phylogenetically clustered according to the metrics NRI and NTI , which indicates that selective processes likely shaped these communities. Furthermore, 17% of these taxa were not detectable in the background soil, even with a robust sequencing depth of approximately 70,000 sequences per sample. These results support the hypothesis that roots select less abundant or possibly rare populations in the soil microbial community, which appear to be lineages of bacteria that have made a physiological tradeoff for rhizosphere competence at the expense of their competitiveness in non‐rhizosphere soil.

Response of temperate lakes to drought: a paleolimnological perspective on the landscape position concept using diatom-based reconstructions - Courtney R. Wigdahl-Perry; Jasmine E. Saros; Jennifer Schmitz; Randy Calcote; James Rusak; Dennis Anderson; Sara Hotchkiss (Journal of Paleolimnology, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Developing Ecosystem Indicators for Responses to Multiple Stressors - Jennifer Boldt; Rebbeca Martone; Jameal Samhouri; Ian Perry; Sachihiko Itoh; Ik Kyo Chung; Motomitsu Takahashi; Naoki Yoshi (Oceanography, 2014)

Nicotine self-administration in the rat: effects of hypocretin antagonists and changes in hypocretin mRNA - Mark G. LeSage; Jennifer L. Perry; Catherine M. Kotz; David Shelley; William A. Corrigall (Psychopharmacology, 2010)

The role of impulsive behavior in drug abuse - Jennifer L. Perry; Marilyn E. Carroll (Psychopharmacology, 2008)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Escalation of i.v. cocaine self-administration and reinstatement of cocaine-seeking behavior in rats bred for high and low saccharin intake - Jennifer L. Perry; Andrew D. Morgan; Justin J. Anker; Nancy K. Dess; Marilyn E. Carroll (Psychopharmacology, 2006)

Ladybird mothers mitigate offspring starvation risk by laying trophic eggs - Jennifer C. Perry; Bernard D. Roitberg (Behavioral Ecology and Sociobiology, 2005)

The cost of being an omnivore: mandible wear from plant feeding in a true bug - Bernard D. Roitberg; David R. Gillespie; Donald M. J. Quiring; Colleen R. Alma; Wade H. Jenner; Jennifer Perry; Jason H. Peterson; Maxence Salomon; Sherah VanLaerhoven (The Science of Nature, 2005)

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)